2016
DOI: 10.1186/s13071-016-1386-8
|View full text |Cite
|
Sign up to set email alerts
|

Cattle tick vaccine researchers join forces in CATVAC

Abstract: A meeting sponsored by the Bill & Melinda Gates Foundation was held at the Avanti Hotel, Mohammedia, Morocco, July 14–15, 2015. The meeting resulted in the formation of the Cattle Tick Vaccine Consortium (CATVAC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 22 publications
0
50
0
2
Order By: Relevance
“…The application of commercial vaccines for the control of cattle ticks demonstrated that tick vaccines also constitute an effective and environmentally sound approach for the control of TBDs . However, despite recent advances in the identification and characterization of candidate tick vaccine antigens, new tick and pathogen‐derived protective antigens need to be identified to increase vaccine efficacy for the control of TBDs . Herein, we review some of the major approaches and strategies that are currently being used for the identification of protective antigens, as well as some future trends to develop improved tick vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The application of commercial vaccines for the control of cattle ticks demonstrated that tick vaccines also constitute an effective and environmentally sound approach for the control of TBDs . However, despite recent advances in the identification and characterization of candidate tick vaccine antigens, new tick and pathogen‐derived protective antigens need to be identified to increase vaccine efficacy for the control of TBDs . Herein, we review some of the major approaches and strategies that are currently being used for the identification of protective antigens, as well as some future trends to develop improved tick vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Subolesin was recently patented with Bm86 as a dual vaccine emulsion at a reported patented efficacy of 100% [53]. This dual vaccine is currently being testing by the CATVAC consortium in Morocco [7]. It is unknown if the varied efficacies of Bm86 will affect the activity of this dual vaccine or whether the short duration of immunity will continue to be an issue as for Bm86-based vaccines.…”
Section: Intracellular Antigensmentioning
confidence: 99%
“…This is otherwise a conserved ribosomal protein, and the peptide region selected had significant sequence differences from the host ortholog. This vaccine has been patented and is under further trial testing also through CATVAC [7,56]. Previously, gene silencing of this intracellular protein was found to be lethal to Haemaphysalis longicornis ticks [57].…”
Section: Intracellular Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the impact of ticks on livestock health and production as well as withdraw their negative public health effects, acaricides, tick handpicking, animal movement control, and vaccination are often applied to tick control strategies [7]. Acaricides are the most effective control measure of ticks and of tick-borne diseases (TBDs) [8].…”
Section: Introductionmentioning
confidence: 99%